Preservasi Preventif: Kegiatan Pendidikan Sebagai Upaya Pelestarian Koleksi di Perpustakaan FIB Unpad - Maharani, Alfina (Ilmu Informasi Perpustakaan dan Kearsipan, 2022)
Preventive preservation is an attempt to prevent damage to a collection done in a library. One of the activities programs found in preventive preservative is a program of educational activities. These activities are carried out to librarians as well as to library users. The study aims to understand the program of educational activities in preventive preservative attempt in the FIB Unpad library. This article USES qualitative descriptive research methods with data collection techniques through literature, interviews and observations. As a result of this study, the fib unpad library conducts a program of educational activities for librarians of formal and nonformal education. Formal education is given through klate and nonformal programs through seminars. The program of educational activities for the user was provided with the effort to stick warning signs and sanction them to unregulated users.